Global Emergency Medicine: A Review of the Literature From 2012. (15th August 2013) - Jacquet, Gabrielle A.; Foran, Mark; Bartels, Susan; Becker, Torben Kim; Schroeder, Erika D.; Duber, Herbert C.; Goldberg, Elizabeth; Cockrell, Hannah; Levine, Adam C.; Hauswald, Mark
Abstract Objectives The Global Emergency Medicine Literature Review (GEMLR) conducts an annual search of peer‐reviewed and grey literature relevant to global emergency medicine (EM) to identify, review, and disseminate the most important new research in this field to a worldwide audience of academics and clinical practitioners. Methods This year, our search identified 4, 818 articles written in six languages. These articles were distributed among 20 reviewers for initial screening based on their relevance to the field of global EM. Two additional reviewers searched and screened the grey literature. A total of 224 articles were deemed appropriate by at least one reviewer and were approved by their editor for formal scoring of overall quality and importance. Results Of the 224 articles that met our predetermined inclusion criteria, 56% were categorized as Emergency Care in Resource‐limited Settings, 18% as EM development, and 26% as Disaster and Humanitarian Response. A total of 28 articles received scores of 16 or higher and were selected for formal summary and critique. Inter‐rater reliability for two reviewers using our scoring system was good, with an intraclass correlation coefficient of 0.625 (95% confidence interval = 0.512 to 0.711). Conclusions In 2012 there were more disaster and humanitarian response articles than in previous years. As in prior years, the majority of articles addressed the acute management of infectious diseases or the care of vulnerable populations such as children and pregnant women.